2015
DOI: 10.1093/annonc/mdu550
|View full text |Cite
|
Sign up to set email alerts
|

A randomized phase II study of the telomerase inhibitor imetelstat as maintenance therapy for advanced non-small-cell lung cancer

Abstract: Maintenance imetelstat failed to improve PFS in advanced NSCLC patients responding to first-line therapy. There was a trend toward a improvement in median PFS and OS in patients with short TL. Short TL as a predictive biomarker will require further investigation for the clinical development of imetelstat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
124
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(130 citation statements)
references
References 19 publications
1
124
0
Order By: Relevance
“…For the role of imetelstat (a telomerase inhibitor) in maintenance therapy has not been well established [20], a sensitivity analysis recalculating the pooled HRs after excluding this trial and those trials at high risk of bias was therefore performed. The probability of publication bias was assessed using funnel plots and Egger test [21].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the role of imetelstat (a telomerase inhibitor) in maintenance therapy has not been well established [20], a sensitivity analysis recalculating the pooled HRs after excluding this trial and those trials at high risk of bias was therefore performed. The probability of publication bias was assessed using funnel plots and Egger test [21].…”
Section: Resultsmentioning
confidence: 99%
“…1, 13 trials met the inclusion criteria and were eligible for the meta-analysis [4][5][6][7][8]13,14,20,[22][23][24][25][26], with a total of 4960 patients. Overall, twelve trials were fully published journal articles [4][5][6][7][8]13,14,20,[22][23][24][25], while one was published as meeting abstract [26].…”
Section: Characteristics Of the Trialsmentioning
confidence: 99%
“…19,20 Less promising results were observed with solid tumors, including breast cancer and non-small cell lung cancer. 21,22 However, a recent Children's Oncology Group phase 1 study of imetelstat for children with recurrent solid tumors observed partial responses in one patient with Ewing sarcoma and one patient with osteosarcoma. 23 Our results indicate that combination therapy may enhance the effect of imetelstat as a single agent.…”
Section: Discussionmentioning
confidence: 99%
“…[11][12][13][14][15][16][17][18] Phase 1 and 2 clinical trials demonstrated a favorable pharmacokinetic and side effect profile for imetelstat, though with mixed clinical results. 14,[19][20][21][22][23] Although telomerase activity is regulated largely at the level of transcription of TERT, the gene that encodes the catalytic component of the telomerase enzyme complex, it has become clear that telomerase regulation is complex and also involves posttranslational modifications, alternative splicing, and binding to chaperone proteins. 24,25 HSP90 plays a key role in the folding and function of TERT and more than 200 other oncogenic proteins including C-RAF, CDK4, AKT/PKB, mutant p53, and HIF-1a.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] However, clinical trials in breast, lung, and pediatric brain cancer were halted due to hematopoietic toxicity that may have resulted from nonselective hTERT inhibition in stem cells. [9][10][11] Trials are now ongoing in myeloproliferative disease with promising results in myelofibrosis and essential thrombocythemia. 12,13 hTERT is the catalytic subunit of the telomerase holoenzyme.…”
Section: Introductionmentioning
confidence: 99%